2008
DOI: 10.1002/ijc.23904
|View full text |Cite
|
Sign up to set email alerts
|

Plasma 25‐hydroxyvitamin D and premenopausal breast cancer risk in a German case‐control study

Abstract: Laboratory and epidemiological data have linked vitamin D to breast cancer prevention. Beside dietary intake, endogenous production of vitamin D substantially contributes to a subject's vitamin D status. Most studies, however, have assessed dietary intake only. Although differential effects of vitamin D on premenopausal and postmenopausal breast cancer have been discussed, this is the first study to investigate the association of plasma 25-hydroxyvitamin D [25(OH)D], as indicator of the overall vitamin D statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(80 citation statements)
references
References 49 publications
5
75
0
Order By: Relevance
“…Other studies have found benefit in reducing breast cancer risk in pre-menopausal women with normal weight, mainly with an intake of 5 µg/day of vitamin D (57,58). Abbas et al (59) found an inverse association between breast cancer in pre-menopausal women and vitamin D levels, without interaction with BMI and family history of breast cancer, also demonstrated among Japanese women. Fedirko et al (60) also demonstrated an inverse association between circulating levels of vitamin D and breast cancer among pre-and post-menopausal Mexican women in a case-control study.…”
Section: Discussionmentioning
confidence: 94%
“…Other studies have found benefit in reducing breast cancer risk in pre-menopausal women with normal weight, mainly with an intake of 5 µg/day of vitamin D (57,58). Abbas et al (59) found an inverse association between breast cancer in pre-menopausal women and vitamin D levels, without interaction with BMI and family history of breast cancer, also demonstrated among Japanese women. Fedirko et al (60) also demonstrated an inverse association between circulating levels of vitamin D and breast cancer among pre-and post-menopausal Mexican women in a case-control study.…”
Section: Discussionmentioning
confidence: 94%
“…Accordingly, when excluding the E3N cohort members from our EPIC-wide analyses, the associations between 25 Our results regarding hormone receptor positive and negative breast cancer subtypes are in agreement with those from most previous studies. One prospective study revealed that 25(OH)D levels might be inversely associated with the risk of ER2=PR2 tumors in particular, 29 and two case-control studies suggested stronger inverse associations between circulating 25(OH)D and the risk of ER2 34,38 or PR2 tumors, 34 when compared to ER1 and PR1 tumors, respectively. However, the numbers of ER2 and PR2 breast cancer cases were rather low in each of these studies.…”
Section: Epidemiologymentioning
confidence: 99%
“…In observational studies, vitamin D deficiency was associated with an increased risk of cancers, such as colorectal cancer (9), lung cancer (10), and breast cancer (11). Also, a recent meta-analysis by Yin and colleagues found a moderate inverse association between vitamin D status and total cancer incidence and mortality (12).…”
Section: Introductionmentioning
confidence: 99%